2011
DOI: 10.1080/08927014.2011.633704
|View full text |Cite
|
Sign up to set email alerts
|

Low concentrations of honey reduce biofilm formation, quorum sensing, and virulence inEscherichia coliO157:H7

Abstract: Bacterial biofilms are associated with persistent infections due to their high resistance to antimicrobial agents. Hence, controlling pathogenic biofilm formation is important in bacteria-related diseases. Honey, at a low concentration of 0.5% (v/v), significantly reduced biofilm formation in enterohemorrhagic Escherichia coli O157:H7 without inhibiting the growth of planktonic cells. Conversely, this concentration did not inhibit commensal E. coli K-12 biofilm formation. Transcriptome analyses showed that hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 50 publications
4
65
0
Order By: Relevance
“…A few studies have attempted to identify the active compounds responsible for the antibiofilm activity of honey (Truchado et al, 2009;Lee et al, 2011;Majtan et al, 2014). Most of these compounds take part in the prevention of biofilm formation, but little information is available regarding compounds that are able to disrupt established wound biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have attempted to identify the active compounds responsible for the antibiofilm activity of honey (Truchado et al, 2009;Lee et al, 2011;Majtan et al, 2014). Most of these compounds take part in the prevention of biofilm formation, but little information is available regarding compounds that are able to disrupt established wound biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the violacein inhibition and bactericidal effect of manuka honey may be attributed to its high sugar content, as seen in a previous study by Lee et al (2011), which proposed that the QSI activity of diluted honey against E. coli O157:H7 was through a mechanism of action where a high sugar concentration Fig. 6 VioA docking studies.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies investigating the QSI properties of various natural sources suggest that phenolic compounds, such as phenolic acids and flavonoids, might be the active component responsible (Annapoorani et al 2012;Lee et al 2011;Singh et al 2009). Other PFs, with low hydroxycinnamic acid content, showed weak or no violacein inhibition properties.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of other virulence genes, quorum sensing genes and genes associated with cell division were also reduced. Lee at al (2011) reported that three types of honey (Korean Acacia, Korean Polyfloral and American Clover honey) at concentrations as low as 0.5% significantly inhibited pathogenic E. coli O157:HA biofilm formation in vitro 40 . Furthermore, low concentrations of the Korean acacia honey reduced the expression of curli genes (csgBAC), quorum sensing genes (AI-2 importer, indole biosynthesis) and virulence genes (LEE genes) in the bacterial strain.…”
Section: Accepted Manuscriptmentioning
confidence: 99%